The variety of actions undertaken in Kielce in favour of the balanced development - Żeber-Dzikowska, Ilona; Buchcic, Elżbieta (Studia Ecologiae et Bioethicae, 2008)
In the article, the information concerning the undertaken actions in favour of the natural environment has been introduced, they refer not only to the changes in the curriculum, but also to the realization of the ecological and sozological presentation in the range of the programme offers dealing with the sources and ecological, cultural and recreation institutions. The best participation of all interested objects, which influence in the straightforward and not straightforward ways on the local communities, is required to introduce such successful politics.